Distração e choque: a experiência da arquitetura na vida cotidiana - Rita de Cassia Lucena Velloso (2007)
This thesis consists in an exploration around the experience caused by an architectural object, assuming as a premise that the field to be investigated is the experience of architecture in everyday life. Considering the nature of an architectural object, the action concerning a man/woman that inhabits is the use as action equivalent to participation. It investigates the nature of such, understanding that this action is not limited to contemplation, whether or not containing some of its elements; it is participation in the object, since its use requires understanding it in a deep and continuous manner. It is also participation towards a political praxis, as performed in public space, reverberating in social relations. Mainly three philosophical works were researched: Walter Benjamins, Henri Lefebvres and the Situationist International. It highlights the conceptual elaboration held by each of them on the architecture, the city and the urban, and, after, the examination of the concept of this experience in their philosophies takes place. The study redoes the arguments about the critique of everyday life, seeking the sources and the concept formulation, as presented in the twentieth century. The city is taken into consideration as a crucial element in the critique of capitalism, specifically in commodity fetishism critique. It is possible to identify the architecture to a commodity-form that is expression of inhabitants everyday life since, within the capitalist commodity production, any architectural object is a result of capital values. Within its complex structures, a large city is nourished by the metabolism of merchandise. The understanding of the city, for each of the three authors researched, takes place according to specific categories in their respective theories: in Walter Benjamin, the phantasmagoria; in Guy Debord, the spectacle; and in Henri Lefebvre, space. It will be a preponderantly hermeneutic approach the theme of everyday life in its correlation with the aesthetic reception of the concept of history in the assembly of the problem that relates the architectural typology with its use. Henri Lefebvre and the Situationist International completed the frame of the work, as there are, in their thoughts, a meeting of two philosophies, phenomenology and materialism. Thus, there is a goal to establish that if it is possible to understand the experience as the ability to understand the world in which we live, urban architecture is one of the cornerstones in the overall texture of this experience. In everyday criticism is the possibility to fight spatial alienation, surpassing the phantasmagoria and the spectacle force in contemporary life, necessarily expressed in its architecture.